PENGARUH MOTIVASI DAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. ADIRA FINANCE CABANG PEKANBARU - Thio Trijoni; Nuryanti '; Taufiqurrahman ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Formulation of the problem in writing this essay is What motivation and leadership simultaneously affect the job satisfaction of employees at PT Adira Finance Cabang Pekanbaru? Is partial motivation affect the job satisfaction of employees at PT Adira Finance Cabang Pekanbaru? Is leadership a partial effect on job satisfaction of employees at PT Adira Finance Cabang Pekanbaru? The population of this study were employees of PT Adira Finance Cabang Pekanbaru, amounting to 268 people. In Slovin sampling method is used to obtain as many as 71 respondents. To determine the perceptions of the dimensions of job satisfaction, the method of data analysis used in this study is using the method of Multiple Linear Regression, F test and t test. Results of research and testing simultaneously known simultaneously, variable motivation , leadership significant effect on satisfaction. There are indicators with an average low of leadership and employee relationships, where employees feel a lack of harmony in the relationship between leaders and subordinates. The results of the study partially motivated significant effect on employee job satisfaction. Motivation in the form of superiors to subordinates approach has not been felt by employees, especially supervisors indifference. In addition, awards to employees who do not perform. Thus, employees who have no achievements strive to continually improve performance resulting into decreased job satisfaction. The results of the research for leadership variables partially significant effect on employee job satisfaction. Low motivation of employees in marketing products proactively savings, lack of initiative, and are still waiting for not doing proactive strategy. If this is allowed to continue would result in a decrease of performance appraisal which impact on the compensation received by the employee so as to reduce employee job satisfaction.Keywords : Motivation, Leadership, Job Satisfaction